Entanglement of Permutation Symmetric State - Duger, Ulam-Orgikh; Masahiro, Kitagawa (Scientific transaction of the National University of Mongolia. Physics, 2022)
We consider an assembly of N indistinguishable two-level atoms, for which a concept of spin- squeezing and entanglement measures can be well defined. Permutation symmetry of such a state allows one to use an entanglement measure called the concurrence as the measures of pairwise and also N-partite entanglement. Dy using these measures, we show that negative pair-spin correlations of the state are quantum ones. It implies the quantumness of a spin-squeezing, which also possesses pair-spin negative correlations. We also provide the entanglement measures of a macroscopic entangled state and an atomic Dicke state for super-radiant and spontaneous emissions.